Impact of strong repeated ground excitation to the on-plan rotation of asymmetric building with various strength and stiffness eccentricities - A., Rashidi; T. A., Majid; A., Faisal; M. I., Adiyanto (IOP Publishing, 2019)
Buildings subjected to torsional effect may result to the floors of the building not only translate laterally but also rotate vertically. Torsional effects may significantly modify the seismic response of buildings, and even cause severe damage or collapse of structures. The current practices in earthquake design is to apply single earthquake on structure during modelling and analysis. However, in real earthquake occurrence, the earthquakes normally occurred repeatedly after the first event. This phenomenon can affect the stiffness and strength of the structural system especially for repeated strong motions. With greater damage expected and lack of time, any rehabilitation action is impractical. Slab rotation, a major response parameter to represent the severity of the torsional response of eccentric systems, is considered. The centre of strength (CR) and centre of stiffness (CS), as two interdependent and important factors to the torsional response of buildings, are investigated via eighty positions of strength eccentricities (er) and stiffness eccentricities (es). Hence, this paper presents the torsional behaviour of a single storey, three-dimensional asymmetric building under the excitation of single and repeated strong ground motions. These motions are applied in the z-direction and analysed for elastic and inelastic conditions. The results are interpreted based on two position models. Position Model A concludes that the effectiveness of CS reduces gradually until CS ratio (es/bz) ≤0.2; thereafter effectiveness of CR increases to cause elastic slab rotation. With repeated ground motion, the magnitude of inelastic rotation is increased; however es/bz ≤0.2 is maintained showing effectiveness of stiffness eccentricity irrespective of nature of ground motion. Position Model B shows that slab rotation is affected by repeated ground motion. Elastic/inelastic analysis under repeated ground motion must be conducted in oppose to current practice, so that the designed structure can undertake the elastic/inelastic demand; especially for the lower CR ratio values.